ANALISIS STRATEGI PEMASARAN DENGAN MENGGUNAKAN METODE SWOT PADA UNIVERSITAS MUHAMMADIYAH TANGERANG - Sena Atmaja; Resy Perwithasari (Universitas Muhammadiyah Tangerang, 2019)
The purpose of this study is to determine the right marketing strategy sothat the number of UMT new students is increasingly based on whatare the strengths, weaknesses, opportunities and threats that arepursued by UMT. How to Understand UMT has great strength, thestrength is questioning because UMT is a Muhammadiyah charitybusiness. UMT also passed a huge opportunity which was high in thepublic interest to continue their education up to college. The mostdominant weakness of UMT is the weak competence of lecturers, whilethe major challenges related to UMT are the national economicconditions that do not support economic improvement and the rapiddevelopment of information technology. The position of the UMTquadrant coordinate in the growth position means that UMT is a strongand potential organization. The recommendations given are progressive,meaning that the organization is in top condition and stable. Related toreally being expanded to continue the development of expansion,growth and improvement, the most appropriate marketing strategy is tosupport the development of strategies, including by improving the qualityof service, both for students, prospective students, by promoting values,Islam and nobility.